The effect of minimal and high flow anesthesia on optic nerve sheath diameter in laparotomic gynecological surgery: Anesthesia on optic nerve sheath diameter - Onur, Anıl; Onur, Tuğba; Karaca, Ümran; Sayan, H Erkan; Yılmaz, Canan; Kılıçarslan, Nermin (Journal of Surgery and Medicine, 2023)
Background/Aim: Optic nerve sheath diameter (ONSD) is a surrogate parameter for intracranial pressure. This study evaluated the effect of anesthetics on ONSD in women undergoing surgery. We aimed to measure the effect of minimal and high flow anesthesia techniques on expiratory/inspiratory oxygen and carbon dioxide fraction values, hemodynamic parameters, and the optic nerve sheath diameter by ultrasonography in open gynecological surgeries. Methods: In the present prospective cohort study, 80 patients who planned laparotomic gynecological surgery were divided into two groups: a high flow of 2 L/min and a minimum flow of 0.5 L/min. Anesthesia was maintained with 50% oxygen-50% air at 2 L/min and desflurane at 1.1 MAC in Group 1 (n=40) and 50% oxygen-50% air at 0.5 L/min and desflurane at 1.1 MAC in Group 2 (n=40). After 10–15 min, group 2 was administered minimal flow with 50–60% oxygen and 40–50% air at 0.5 L/min desflurane, and 10 min before the end of the surgery, the patients were switched to high flow with 50% oxygen-50% air at 2 L/min. Results: Decreasing heart rates were higher in Group 2 (T0 P=0.001, T2 P=0.007, T3 P=0.035). There was a significant positive correlation between EtCO2 at the 60th min and optic nerve sheath diameter measurements in the minimal flow group (left ONSD r=0.440, P=0.004, right ONSD r=0.473, P=0.002). Although inspiratory oxygen values in Group 2 did not fall below 32%, it was lower than Group 1 except for the last measurement time. Conclusion: Minimal flow anesthesia is as safe as high flow in terms of effects on optic nerve sheath diameter and oxygenation parameters in laparotomic gynecological surgery.